Tokopedia X Blackpink Advertising Discourse Analysis - Fitri Dianitasari (Universitas Airlangga, 2022)
Advertising is an interesting discourse to attract public attention. Advertising itself has undergone changes where lately it has focused on the approach side to products, product symbols, personal, and market segments. Not a few online buying and selling sites use advertisements to promote trademarks, for example Tokopedia. Tokopedia provides a variety of products that are needed. Tokopedia Advertising Discourses are produced to attract consumers to use or buy the products offered. The emergence of popular artists in online store advertisements is a current trend. No need to be surprised if Indonesia uses Kpop artists in marketing their products. This study used a descriptive qualitative method. The data is taken from Tokopedia's e-commerce advertisement in collaboration with Korean girl group Blackpink. The object used in this research is an advertisement from the online shop Tokopedia collaborating with a Korean girl group, namely BLACKPINK with the theme Tokopedia x Blackpink by discussing the discourse structure of Teun A. Van Dijk in 3 aspects, namely superstructure, micro structure, and macro structure. Discourse analysis research on Tokopedia advertisements using Van Dijk Theory shows that the three parts has succesfully appear in Tokopedia advertisements. From the analysis that has been done, it shows that the material owned by Tokopedia ads is complete and the advertisement is able to describe the message that the advertiser wants to convey to the audience which are the benefits and special events.